Optimal power demand curve: a case study in Universiti Putra Malaysia - Lawal, Sani Mohammed; Hizam, Hashim; Toudeshki, Arash Mohammadi; Gomes, Chandima; Jasni, Jasronita (IEEE, 2012)
The necessitation in the optimal power demand model, make it an impetus to present this work as a glaring path in determining the optimum power demand curve, using the available data of a substation. The data are used to find the equation and its coefficients of determination that can give the best-fit curve of the power demand of a substation, based on the available data. This will produce a model that can be validated by comparing the data and figured out the equation.